PF-25 Cub Scout Leader Gathering for Zoonoses Awareness: A model for Community Participatory Program for Zoonotic Diseases Control in Indonesia - Fadjar Satrija; Sri Murtini (Hemera Zoa, 2018)
Outbreaks of zoonotic diseases such as avian influenza and rabies during the last decade have caused fatalities and fear among people in Indonesia. The Government of Indonesia, the World Health Organization (WHO), the Food and Agriculture Organization (FAO), as well as other international and domestic NGOs have been working together to control those diseases and prevent human pandemic. However, the zoonotic disease control programs will not succeed without active participation of local communities including young people.Indonesia Scout Movement (Gerakan Pramuka) is a non-formal educational organization having more than 20 million members that serve educational process outside the school and outside the family using basic principles and methods of scouting (GOI 2010). Members of Gerakan Pramuka consist young people of different age categories namely  Cub Scouts/Siaga (ages 7 to 10 y.o), Scouts/ Penggalang (ages 11 to 15 y.o), Rover Scouts/ Penegak  (ages 16 to 20 y.o), Pandega (ages 21 to 25 y.o), and Adult members/Pembina  (ages > 25 y.o, or married person).Nowadays, Gerakan Pramuka has more than 20 millions members distributed in all districts in Indonesia, and thus may become a potential media to enhance young people awareness on zoonotic diseases control programs. Dissemination of information on the diseases and its prevention can be done through scout regular events such as Pesta Siaga  (Cub Scout Gathering), Jamboree (Scout Gathering), Raimuna (Rover Scout Gathering), and Karang Pamitran (Adult Scout member Gathering).Faculty of Veterinary Medicine, IPB, in collaboration with IPB Student Scouting Activity Unit, has developed a model for the community participatory program for zoonotic diseases control in Indonesia through scouting activities. Cub Scout Leader Gathering for Avian Influenza Awareness is a scout event that designed as a method for dissemination of information regarding prevention of avian influenza transmission to school age children and their relatives.